Effect of auditing: Evidence from variability of stock returns and trading volume - Charles J. P. Chen; Bin N. Srinidhi; Xijia Su (China Journal of Accounting Research, 2014)
Although the benefits of auditing are uncontroversial in developed markets, there is scant evidence about its effect in emerging economies. Auditing derives its value by increasing the credibility of financial statements, which in turn increases investors' reliance on them in developed markets. Financial statement information is common to all investors and therefore increased reliance on it should reduce divergence in investors' assessment of firm value. We examine the effect of interim auditing on inter-investor divergence with a large sample of listed Chinese firms and find that it decreases more for firms whose reports are audited compared to non-audited firms. This finding suggests that investors rely more on audited financial information. Results of this study are robust to variations in event window length and specification of empirical measures.
Keywords: 650; Auditing; Inter-investor divergence; Variability of stock returns; Trading volume